The Lambda Method for the GNSS Compass - Teunissen, Peter (Versita, 2006)
Global Navigation Satellite System carrier phase ambiguity resolution is the key to high precision positioning and attitude determination. In this contribution we consider the GNSS compass model. We derive the integer least-squares estimators and discuss the various steps involved in the ambiguity resolution process. This includes the method that has successfully been used in (Park and Teunissen, 2003). We emphasize the unaided, single frequency, single epoch case, since this is considered the most challenging mode of GNSS attitude determination.